Twelve Year Outcomes of Oxinium Total Knee Arthroplasty Compared to the Same Cobalt Chrome Prosthesis: A Matched Cohort of 17 577 Cases from the AOANJRR. Issue 2 (16th February 2016) - Vertullo, Christopher; Lewis, Peter; Graves, Stephen; Kelly, Lan; Myers, Peter
Introduction: Alternative bearings surfaces to Cobalt Chrome (Co-Cr), such as Oxidised have been introduced in an attempt to reduce polyethylene wear and hence decrease TKA loosening and lysis. While non-comparative reports have been described as promising, no short or long term clinical studies exists showing the superiority of Oxinium on a polyethylene bearing surfaces. In this study, we investigate the long-term outcomes of Oxinium and Co-Cr TKR in a "like for like" or matched cohort analysis of the Genesis II design (Smith & Nephew, Memphis, TN, USA). Using data from a large national joint replacement registry we selected cohorts that used only the cruciate retaining design, with the same method of fixation and polyethylene type, differing only in the femoral component bearing surfaces. Our primary hypothesis was that Oxinium TKA would have a lower cumulative percent revision than the same Co-Cr prosthesis at 12 years for all causes of revision. Our secondary hypothesis was that Oxinium TKA would have a lower loosening/ lysis rate and lower rate of non-infective revision than the same Co-Cr prosthesis at 12 years. Methods: Cumulative percent revision and revision diagnosis data were obtained from the Australian Orthopaedic Association National Joint Replacement Registry (AOANJRR) from 1 September 1999, until 31 December 2013. Results: At 12 years the cumulative percent revision of the Co-Cr Genesis II of 4.8 % (95%: CI 4.2, 5.4) for all causes was not statistically different to the Oxinium Genesis II CPR of 7.7 % (95%: CI 6.2, 9.5) (For the entire period, Hazard Ratio = 1.09 (95%: CI 0.92, 1.29), p = 0.329). The CPR for all causes was not different in the under 55 years old age group (Figure 3) (HR= 1.06 (0.68, 1.66) p=0.798).). Subgroup analysis of the CPR for loosening /lysis in both groups overall was not different (HR= 0.87 (95%: CI 0.61, 1.26), p = 0.461) Subgroup analysis of all causes of revisions excluding infection in both groups overall was not different (HR = 0.87 (95%: CI 0.71, 1.06), p = 0.155) . No difference in CPR was found between the Oxinium and Co-Cr groups for any age category for all causes of revision, loosening/lysis or non-infective causes, except for loosening/lysis in the >75 years old group (p=0.033). In these patients, Oxinium TKA had a higher CPR due to uncertain reasons. Conclusions: In this AOANJRR age stratified matched cohort study, Oxinium femoral components did not reduce revision rates due to all causes, loosening/lysis or when infection as a cause of revision was removed, compared to the same Co-Cr femoral component, across all age groups including patients who were under 55 years of age.